Umbilical artery cord blood glucose predicted hypoglycemia in gestational diabetes mellitus and other at-risk newborns - Yuan Wang; Huahua Liu; Leilei Zhang; Xin Wang; Mingbo Wang; Zhifang Chen; Feng Zhang (BMC Endocrine Disorders, 2023)
Abstract Background To explore the value of umbilical artery cord blood glucose (UACBG) in predicting hypoglycemia in gestational diabetes mellitus (GDM) and other at-risk newborns, and to provide a cut-off UACBG value for predicting hypoglycemia occurrence. Methods In this prospective study, we enrolled at-risk infants delivered vaginally, including neonates born to mothers with GDM, premature, macrosomic, and low birth weight. We separated the infants into GDM group and other at-risk group. All subjects underwent UACBG measurement during delivery. Neonatal peripheral blood glucose measurement was performed at 0.5 and 2 h after birth. The predictive performance of UACBG for neonatal hypoglycemia was assessed using receiver operating characteristic curve (ROC), area under curve (AUC), sensitivity, specificity, negative predictive value (NPV) and positive predictive value (PPV). Results 916 newborns were included, with 538 in GDM group and 378 in other at-risk group. 85 neonates were diagnosed hypoglycemia within 2 h after birth, including 36 belonging to GDM group and 49 to other at-risk group. For hypoglycemia prediction within 2 h, the best cut-off of UACBG was 4.150 mmol/L, yielding an AUC of 0.688 (95% CI 0.625–0.751) and a NPV of 0.933. In detail, the AUC was 0.680 in GDM group (95% CI 0.589–0.771), with the optimal cut-off of 4.150 mmol/L and a NPV of 0.950. In other at-risk group, the AUC was 0.678(95% CI 0.586–0.771), the best threshold was 3.950 mmol/L and the NPV was 0.908. No significant differences were observed between GDM group and other at-risk group in AUC at 0.5 h, 2 h and within 2 h. Conclusions UACBG has a high NPV for predicting neonatal hypoglycemia within 2 h after birth. It was implied that individuals with cord blood glucose levels above the threshold were at lower risk for hypoglycemia. UACBG monitoring provides evidence for subsequent classified management of hypoglycemia.